Powering Elementary Civics Education: Enhancing Active Learning and Performance: Meningkatkan Pembelajaran Aktif dan Prestasi Akademik Siswa SD melalui Microsoft PowerPoint: Studi Eksperimental pada Pendidikan Kewarganegaraan - Mauludiana Rahmawati; Machful Indra Kurniawan (Universitas Muhammadiyah Sidoarjo, 2023)
This research addresses the issue of passive student engagement and teacher-centered learning approaches in primary schools. To overcome these challenges, the study employs Microsoft PowerPoint as an instructional medium to enhance the learning experience. A Pre-Experimental Design research method is employed, conducted at SD Negeri Pejangkungan with thirty fourth-grade students as participants. Data collection involves the use of tests, and the obtained results are subjected to t-test analysis. The findings reveal a significant positive impact of utilizing Microsoft PowerPoint media on students' civics learning outcomes, as indicated by tcount (24.686) exceeding ttable (2.045). Additionally, eta squared analysis demonstrates a considerable influence of Microsoft PowerPoint media on learning outcomes (0.95>0.14). These results emphasize the potential of Microsoft PowerPoint as an effective tool to promote active learning and enhance students' academic achievements in various educational settings. Highlights: Active Engagement: This research explores the use of Microsoft PowerPoint as a means to promote active learning among elementary students, addressing the issue of passive student engagement in the classroom. Academic Improvement: The study investigates the impact of utilizing Microsoft PowerPoint on students' academic performance, specifically focusing on civics education, to determine the effectiveness of this instructional medium. Experimental Design: The research employs a Pre-Experimental Design methodology, conducted at SD Negeri Pejangkungan with fourth-grade students, to gather data through tests and analyze the outcomes using statistical measures such as t-tests and eta squared. Keywords: Active learning, Academic performance, Microsoft PowerPoint, Experimental study, Civics education.